Moroccan Mirages: Agrarian Dreams and Deceptions, 1912-1986 - WILL DAVIS SWEARINGEN (Princeton University Press, 2014)
This book examines the dreams and deceptions underlying agricultural development in Morocco. Focusing primarily on the policy-making process, it reconstructs the decision-making environments in which major policies were formulated, and explores the rationale behind policy. Its purpose is, first, to help elucidate policy making during the French protectorate period (1912-56) and analyze the continuing impact of colonial policies; second, to explain the failure of agricultural development efforts since independence—failure that is rapidly precipitating political and economic crisis. Conventional wisdom on European colonization and national development processes in former colonies is a surprisingly rickety construction of premature conclusions. Far too few actual case studies have been conducted. Furthermore, generalizations have been drawn primarily from the British colonial realm. The former French empire has been relatively ignored, despite the fact that British and French colonialism were "as different as chalk from cheese."1 Unfortunately, several dubious assumptions have evolved into truisms. For example, it is commonly assumed that the European colonial powers were motivated primarily by hardheaded economic logic in the development of their colonies. As will be shown, this assumption is largely false for French development policies in Morocco. Indeed, to believe that French policy makers were shrewd businessmen completely misses what was perhaps the most striking feature of French colonialism in Africa: "the enormous disparity between the hopelessly unrealistic objectives of French policy-makers and the actual results of their policies.